Implementing Genre Based Approach to Teach Writing for College Students - Asih Rosnaningsih; Dayu Retno Puspita (Universitas Muhammadiyah Surabaya, 2020)
Abstract. Teaching writing for English foreign students offers very interesting challenges for the few past years, especially in the Indonesian learning situation. The teacher himself must ensure the students understand as well as produced good products of writing in various text types. Based on that assumption, this research described the undergoing process of students in their learning to write using Genre Based Approach. This research is presented qualitatively with the subject of Indonesian college students who are taking English class. The GBA approach in this study developed into four phases that are Building knowledge of the field (BKOF), Modelling the text, Joint Construction of The Text (JCOT), and Independent Construction of Text (ICOT). After students were taught using this approach, they filled out questionnaires to find out the suitability of the GBA steps with the real practice in learning to write. In summary, the GBA approach is applicable and suitable in the practice of teaching writing.